Reverse geroscience: how does exposure to early diseases accelerate the age‐related decline in health?. Issue 1 (1st December 2016) - Kohanski, Ronald A.; Deeks, Steven G.; Gravekamp, Claudia; Halter, Jeffrey B.; High, Kevin; Hurria, Arti; Fuldner, Rebecca; Green, Paige; Huebner, Robin; Macchiarini, Francesca; Sierra, Felipe
Abstract : Aging is the major risk factor for both the development of chronic diseases and loss of functional capacity. Geroscience provides links among the biology of aging, the biology of disease, and the physiology of frailty, three fields where enormous progress has been made in the last few decades. While, previously, the focus was on the role of aging in susceptibility to disease and disability, the other side of this relationship, which is the contribution of disease to aging, has been less explored at the molecular/cellular level. Indeed, the role of childhood or early adulthood exposure to chronic disease and/or treatment on accelerating aging phenotypes is well known in epidemiology, but the biological basis is poorly understood. A recent summit co‐organized by the National Institutes of Health GeroScience Interest Group and the New York Academy of Sciences explored these relationships, using three chronic diseases as examples: cancer, HIV/AIDS, and diabetes. The epidemiological literature clearly indicates that early exposure to any of these diseases and/or their treatments results in an acceleration of the appearance of aging phenotypes, including loss of functional capacity and accelerated appearance of clinical symptoms of aging‐related diseases not obviously related to the earlier event. The discussions at the summit focused on the molecular and cellular relationships between each of these diseases and the recently defined molecular and cellular pillars of aging. Two major conclusions from the meeting include the desire to refine an operational definition of aging and to concomitantly develop biomarkers of aging, in order to move from chronological to physiological age. The discussion also opened a dialogue on the possibility of improving late‐life outcomes in patients affected by chronic disease by including age‐delaying modalities along with the standard care for the disease in question.